The Cost of Dodd-Frank Act for Commercial Banks - Cruz, Darik; Feliberty, Miguel Vicens (International Journal of Economics and Financial Issues, 2023)
The intent of this article is to explain how the Dodd-Frank Act impacts banks and puts a spotlight on the cost of this Act to financial institutions, especially small banks. As part of the discussion, federal agencies are described as the regulators in charge of supervising strict compliance and adherence to the applicable law. Through our research it is apparent that part of the reporting costs is transferred to the consumers in different fees and charges, which impacts the bank’s competitiveness. We depart from the premise that large banks could transfer these costs to consumers easier, because they have a critical mass of clients and products, enough to cover the additional expenses incurred when conforming with the regulation. Additionally, we analyze the cost of implementation from perspective of size which shows a substantial difference to institutions of various sizes. We conclude the paper recommending additional research and primary data collection that could contribute to a better understanding of the cost of the Dodd-Frank Act.